Postcode Lotteries in Public Health - The NHS Health Checks Programme in North West London - McCoy David C; May Katherine F; Graley Clare EM (BMC, 2011)
Abstract Background Postcode lotteries in health refer to differences in health care between different geographic areas. These have been previously associated with clinical services. However there has been little documentation of postcode lotteries relating to preventative health care services. This paper describes a postcode lottery effect in relation to the NHS Health Checks Programme (a national cardiovascular screening programme in England) in eight PCTs in the North West sector of London. Methods A descriptive cross-sectional analysis of the Health Checks Programme was carried out in eight PCTs in North West London using a structured data-collecting instrument. Results The analysis found variation in the implementation of the national Health Checks Programme in terms of: the screening approach taken; the allocated budget (which varied from £69,000 to £1.4 million per 100,000 eligible population); payment rates made to providers of Health Checks; tools used to identify and measure risk of cardiovascular disease and diabetes; monitoring and evaluation; and preventative services available following the health check. Conclusions This study identifies a postcode lottery effect related to a national public health programme. Although it is important to allow enough flexibility in the design of the Health Checks Programme so that it fits in with local factors, aspects of the programme may benefit from greater standardisation or stronger national guidance.